Nanostructured mesoporous carbon polyethersulfone composite ultrafiltration membrane with significantly low protein adsorption and bacterial adhesion. (January 2017) - Orooji, Yasin; Faghih, Maryam; Razmjou, Amir; Hou, Jingwei; Moazzam, Parisa; Emami, Nahid; Aghababaie, Marzieh; Nourisfa, Fatemeh; Chen, Vicki; Jin, Wanqin
Abstract: A novel polyethersulfone (PES) ultrafiltration membrane containing 0.05–2.00 wt% of synthesized mesoporous carbon nanoparticles (MCNs) was prepared via the phase inversion technique. The structures and properties of MCNs were characterized using a variety of analytic techniques. The MCNs showed the surface area of 1396.8 m 2 /g and the highest pore size of around 1 nm. The effect of incorporation of MCNs on the composite membrane morphology and performance was investigated through pure water flux, protein adsorption, and bacterial adhesion resistance tests. The membrane's anti-fouling performances were determined under constant-pressure operation at 100 kPa in a dead-end module. The as-prepared nanocomposite membranes were also studied in terms of morphology, structure and surface chemistry. Generally, the incorporation of MCNs into the polymeric membrane improved the pure water flux. The composite membrane containing 0.20 wt% MCNs exhibited the highest antifouling, protein adsorption resistance, and bacterial attachment inhibition property. The incorporation of the MCNs into the membranes introduces a different strategy of inhibiting biomolecule adsorption and bacterial attachment to the membrane surface, instead of killing the bacteria which may lead to more severe membrane fouling by the intracellular substances. Graphical abstract: